Ordered nanostructures by colloidal self-assembly - Teh, Lay Kuan (2010)
This research is focused on the fabrication of optically active three-dimensional (3D) ordered nanostructures by the cost-effective colloidal self-assembly (CSA) approach, and their applications in high performance photonic microlasers and efficient light sources for the next era of integrated optoelectronics. This includes detailed consideration essential to the building of high-quality 3D photonic crystals (PhCs) for the control of light in the ultraviolet (UV) and visible regimes, methods for measuring photonic bandgap (PBG), and the engineering of defects. The colloidal PhCs (a. k. a. artificial opals) should have sufficient dielectric contrast for opening a complete PBG, low defect density for extending long range crystallinity and the possibilities to introduce intentional defects. The thesis begins with a study on growth imperfections in polystyrene (PS) opals grown by the widely-used vertical convective self-assembly approach. Here, the growth pattern is attributed to the dynamic balance between surface tension forces due to the change in the contact angle with time, which results in a "stick-slip" motion of the meniscus growth front. These macroscopic imperfections have been reduced to produce single-crystal opals over centimeter-square areas. This forms the basis for the realization of functional PBG materials. The PS opals then serve as templates for the fabrication of two different optically active 3-D PhCs, (i) ZnO inverse opal (ii) and the lattice-matched ZnO-PS hetero-opal. Both systems have been prepared by infiltrating PS opaline templates using the costeffective, vacuum-less, and aqueous-based electrodeposition technique, which produces highly dense materials for high filling fraction. Unlike most previous studies on incorporating light-emitting elements into the body of an opal or over a small fraction of the opal surface, this research introduces an "emissive" PhC, where the light emitters (ZnO) constitute the dielectric framework of the PhC. These PhCs possess photonic pseudogaps tunable in the UV to visible spectrum, while effective photonic pseudogaps emerge in the hetero-opal. To reveal the key factors for enhanced photonic pseudogap characteristics, this thesis presents the first systematic comparative study, both experimentally and theoretically, on the optical characteristics of opals and inverse opals.